2009
DOI: 10.1051/0004-6361/200809945
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic star-formation history from a non-parametric inversion of infrared galaxy counts

Abstract: Aims. This paper aims at providing new conservative constraints on the cosmic star-formation (SF) history from the empirical modeling of recent observations in the mid and far infrared. Methods. We present a new empirical method based on a non-parametric inversion technique. It primarily uses multi-wavelength galaxy counts in the infrared and sub-mm (15, 24, 70, 160, 850 μm), and it does not require any redshift information. This inversion can be considered as a "blind" search for all possible evolutions and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
123
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 51 publications
19
123
3
Order By: Relevance
“…1, we overlay recent models onto the observed PACS counts. We include in this collection the Lacey et al (2010) Gruppioni and Lagache et al (2004) overestimate the amplitude of the number counts peak in both bands, while Franceschini et al (2010) and Le Borgne et al (2009) reproduce the counts fairly well only in one channel (100 and 160 μm, respectively). It is worth recalling that to date most of these models have been fine-tuned to reproduce mid-IR and sub-mm statistics, while a big gap in wavelength was affecting far-IR predictions.…”
Section: Discussionmentioning
confidence: 99%
“…1, we overlay recent models onto the observed PACS counts. We include in this collection the Lacey et al (2010) Gruppioni and Lagache et al (2004) overestimate the amplitude of the number counts peak in both bands, while Franceschini et al (2010) and Le Borgne et al (2009) reproduce the counts fairly well only in one channel (100 and 160 μm, respectively). It is worth recalling that to date most of these models have been fine-tuned to reproduce mid-IR and sub-mm statistics, while a big gap in wavelength was affecting far-IR predictions.…”
Section: Discussionmentioning
confidence: 99%
“…We first start from a simulated catalog generated from the model of Le Borgne et al (2009) that best fits number counts of sources at 15, 24, 70, 160, 850 μm. This catalog, which contains all infrared sources that should be observed over a field of 283 arcmin 2 with 0 < z < 5, reproduces the observed infrared LF up to z ∼ 1.3 (e.g., see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these correlations SED libraries have been developed and extensively used to estimate the total infrared luminosity of galaxies (e.g., Chary & Elbaz 2001;Lagache et al 2003;Dale & Helou 2002, hereafter CE01, LDP, and DH 1 respectively). However, it is not clear that these local templates are suitable to describe the spectral properties of distant galaxies (Papovich et al 2007;Daddi et al 2007b;Le Borgne et al 2009). To study this issue, we decided to characterize the observed 24 μm vs. 70 μm correlation and compare it to the predictions of standard SED libraries.…”
Section: The Total Infrared Bolometric Correctionmentioning
confidence: 99%
“…95.6% of them either have a spectroscopic (67.2%, Cohen et al 2000;Wirth et al 2004;Barger et al 2008) or photometric (28.3%, from Le Borgne et al 2009) redshift. Herschel detects a third of them (493 galaxies) in at least one of the PACS or SPIRE passbands.…”
Section: Sample and Methodsmentioning
confidence: 99%